Aleksander Scibor-Rylski w tandemach: z Kawalerowiczem, Kutzem i Hofmanem - Śmiałowski , Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Aleksander Ścibor-Rylski was one of the greatest Polish scriptwriters, who in addition to numerous films based on his texts, left behind a trove of abandoned scripts. This article introduces Ścibor-Rylski as a highly versatile author, as exemplified by three scripts he wrote: Wczasy pod lipą [Lime Tree Holiday], Zaułek św. Sebastiana [Saint Sebastian Alley] and Stara baśń [An Ancient Tale]. Each of these scripts was written in a different convention and each was ordered by a different director, hence the title of this article – Aleksander Ścibor-Rylski in tandem with Kawalerowicz, Kutz and Hoffman. Apart from an analysis of the three scripts, the article describes the way they evolved, Ścibor-Rylski’s favourite stylistic clues and the reasons they remained unfinished.